A study of safety and efficacy of vitamin D3 supplementation in pregnancy - Mirza, Huma Afzal; Arzoo, Nigare; Prajapati, Pooja (International Journal of Advances in Medicine, 2024)
Background: Vitamin D is a lipid-soluble prohormone that is vital for the maintenance of bone and muscle health. Vitamin D deficiency is an unrecognized epidemic, common in all age groups and is associated with preeclampsia, gestational diabetes, preterm birth, early labour and pregnancy loss. Methods: Our study was conducted in Batra hospital and medical research centre, New Delhi from October 2018 to May2019. 126 women were taken, of those seen before 20 weeks of pregnancy who received vitamin D3 supplementation comprised of study group and control group were those who came directly for delivery and without vitamin D3 level done. The outcomes measured were vitamin D3 level at 20 weeks, at delivery, in cord blood and clinical outcomes like pre-eclampsia, gestational diabetes, preterm delivery. Results: Gestational hypertension was seen in 4 (6.3%) of subjects while in control group it was seen in 11 (17.5%), Gestational diabetes was seen in 3 (4.8%) women while it was observed in 10 (15.9%) women of control group. Premature rupture of membranes was seen in 2 (3.2%) women in study group and 8 (12.7%) women of control group. Vitamin D level at the time of delivery in study group was significantly higher than control group (56.84±15.78 versus 18.12±8.97ng/ml). Conclusions: Preterm labor, low birth weight and preeclampsia were uncommon in the subjects and the administered vitamin D3 dose had no adverse effects but more research with larger sample size is strongly urged to assess the safety and effect of vitamin D3 supplementation.